A Novel Membrane Protein-Specific Serine/Threonine Kinase: Tissue Distribution and Role in Sperm Maturation. (1st March 2012) - Nath, Debjani; Bhoumik, Arpita; Das, Sujoy; Bhattacharyya, Debdas; Dungdung, Sandhya R.; Majumder, Gopal C.
Abstract : Our recent studies have described for the first time the purification of an ectoprotein kinase to apparent homogeneity using caprine sperm as the model. Purified ectokinase (CIK) is a novel membrane protein-specific kinase that phosphorylates serine and threonine residues of ectophosphoproteins. This study, using ELISA based on ecto-CIK antibody demonstrates that ecto-CIK level is remarkably higher in the sperm membrane than in the cytosol. The epididymal sperm maturational event as well as sperm vertical velocity is associated with a significant increase in the ecto-CIK level. Ecto-CIK, the membrane protein-specific kinase, is also present in all the tissues tested and is predominantly localized in the cell membrane. Ubiquitous localization of the novel kinase on the mammalian cell membrane suggests that the kinase may play pivotal role in gamete as well as somatic cell regulation by modulating membrane biology through serine/threonine phosphorylation of specific membrane proteins located in the ectodomains.